Reported Exposures Among In-Person Workers With Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) Infection in 6 States, September 2020–June 2021 . (19th June 2022) - Free, Hannah; Luckhaupt, Sara E; Billock, Rachael M; Groenewold, Matthew R; Burrer, Sherry; Sweeney, Marie Haring; Wong, Jessie; Gibb, Kathryn; Rodriguez, Andrea; Vergara, Ximena P; Cummings, Kristin J; Lavender, Antionette; et al.
Abstract: Background: Surveillance systems lack detailed occupational exposure information from workers with severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection. The National Institute for Occupational Safety and Health partnered with 6 states to collect information from adults diagnosed with SARS-CoV-2 infection who worked in person (outside the home) in non-healthcare settings during the 2 weeks prior to illness onset. Methods: The survey captured demographic, medical, and occupational characteristics and work- and non–work-related risk factors for SARS-CoV-2 infection. Reported close contact with a person known or suspected to have SARS-CoV-2 infection was categorized by setting as exposure at work, exposure outside of work only, or no known exposure/did not know. Frequencies and percentages of exposure types are compared by respondent characteristics and risk factors. Results: Of 1111 respondents, 19.4% reported exposure at work, 23.4% reported exposure outside of work only, and 57.2% reported no known exposure/did not know. Workers in protective service occupations (48.8%) and public administration industries (35.6%) reported exposure at work most often. More than one third (33.7%) of respondents who experienced close contact with ≥10 coworkers per day and 28.8% of respondents who experienced close contact with ≥10 customers/clients per day reported exposures at work. Conclusions: Exposure to occupational SARS-CoV-2 was common among respondents. Examining differences in exposures among different worker groups can help identify populations with the greatest need for prevention interventions. The benefits of recording employment characteristics as standard demographic information will remain relevant as new and reemerging public health issues occur. Abstract : Almost one fifth of respondents (19.4%) reported exposure to someone with coronavirus disease 2019 at work. Examining differences in exposures among worker groups by recording occupational characteristics can help identify populations with the greatest need for interventions.